PENGGUNAAN MODEL KOOPERATIF TIPE STAD PADA PEMBELAJARAN TARI PIRING DUA BELAS DI SMA NEGERI 1 KALIREJO LAMPUNG TENGAH - Devi Nurmalasari; Fitri Daryanti; Muhammad Fuad; Hasyimkan Hasyimkan (Jurnal Seni dan Pembelajaran, 2013)
AbstractThe objektives of this reseach are to describe the use of the use of stad type of cooperatif model on learning and to describe the result of studen in achievement tari piring dua belas at class XII IPA 2 in SMA Negeri 1 Kalirejo.The research method was descriptive qualitative. The theory which is use were learning and STAD type of cooperative model. The sources of this research were the teacher of arts and culture and the students of class XII IPA 2 which consists of 35 student. The data collecting techiques which is use was observation, dokumentation in form of photo and field note, interview which was done with the teacher of arts and culture and student, practice test and obsevation, student activity, and the observasion of teacher activity.In conducted STAD type of cooperative model on learning tari piring dua belas.. Teacher divide the student into several groups, by using lottery and be define the leader of each group. During th steps and the axact gesture teacher learning process, each group looks antusis in demonstrating tari piring dua belas, but in the implementation still having the weakness that is students still depend the leader of their group.The result of students learning in demonstrating tari piring dua belas at SMA Negeri 1 Kalirejo, include on the category good. It is consider from the students dance ability on each aspects in remembering the gesture steps, include on the category good. The use of property (plate) include on the category very good. The exact gesture with the music include on the category good.Key word : model cooperatif, result, education, tari piring dua belas